Pengawasan dan Penegakan Hukum Pajak terhadap Praktik Penghindaran Pajak Berganda (Studi Kasus PT Asian Agri Group) - Djatmiko, Sulis; Dharmasetya, Lani (Neolectura, 2025)
This research aims to find out how the causal factors of tax avoidance can occur, then to find out how supervision and law enforcement against the practice of tax avoidance. The type of research used in this writing is normative juridical research which involves the study of theories, as well as relevant regulations related to the research topic. From this research, it is concluded that the main cause of tax avoidance practices, as in the case of PT Asian Agri Group (AAG), is the existence of legal loopholes in the regulation or taxation system that makes taxpayers take advantage of these legal loopholes to avoid their tax obligations. For example, Article 44B of Law No. 7 of 2021 concerning Harmonization of Tax Regulations which opens opportunities for tax crimes to be resolved out of court. Transfer pricing, tax havens, thin capitalization, as well as treaty shopping are the most common methods used by taxpayers to conduct tax avoidance. Because of this, law enforcement against tax avoidance practices is needed by tax authorities by closing legal loopholes and conducting strict supervision of taxpayers suspected of avoiding taxes.